2016
DOI: 10.5586/asbp.3519
|View full text |Cite
|
Sign up to set email alerts
|

The spring has arrived: traditional wild vegetables gathered by Yarsanis (Ahl-e Haqq) and Sunni Muslims in Western Hawraman, SE Kurdistan (Iraq)

Abstract: Kurdistan represents a crucial region in the Middle East for understanding patterns of human evolution in the use of food plants and especially wild vegetables as well as for assessing the influences of the major, surrounding bio-cultural macro-area.In this research, an ethnobotanical filed study focusing on wild vegetables traditionally gathered and consumed during the spring was conducted in a few villages of the Western Hawraman area, in South Kurdistan (Iraq), both among Sunni Muslims and Yarsanis (Ahl-e H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 26 publications
7
30
0
Order By: Relevance
“…The plant can also be dried and consumed during the winter. This detoxification process has been previously reported in ethnobotanical studies conducted near this area [75,97,98]. An ethnobotanical study in a nearby region [33] reported the consumption of Ranunculus fenzlii Boiss.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The plant can also be dried and consumed during the winter. This detoxification process has been previously reported in ethnobotanical studies conducted near this area [75,97,98]. An ethnobotanical study in a nearby region [33] reported the consumption of Ranunculus fenzlii Boiss.…”
Section: Discussionsupporting
confidence: 65%
“…The obtained data were compared with the previously reported ethnobotanical and wild edible plant studies conducted in Turkey and its neighboring countries [94][95][96][97][98] showed a common distribution and usage pattern in Hasankeyf that was similar to the ones reported in previous studies in Turkey and neighboring countries [94][95][96][97][98].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…To maintain this knowledge, supporting local culture and including traditional ecological knowledge in the education of the young generation must be the focus of conservation programs [33,82]. Additionally, as the locals considered the collected species an important entity for their well-being, therefore, such species shall be urgently evaluated for its pharmacological and nutraceutical potential [83].…”
Section: Commercialization and Conservationmentioning
confidence: 99%